2019
DOI: 10.1111/jvh.13214
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to care for people who inject drugs: Qualitative evaluation of project ITTREAT—An integrated community hepatitis C service

Abstract: Achieving hepatitis C virus (HCV) elimination by 2030 requires an increased linkage to care for people who inject drugs (PWID). Project ITTREAT was established to mitigate barriers to HCV care by providing an integrated service within a local drug and alcohol treatment centre. This study aimed to explore the experiences of clients and staff involved in Project ITTREAT and assess the facilitators and barriers to a community-based HCV service. Between October 2014 and April 2016, drug and alcohol treatment atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
(47 reference statements)
1
22
0
1
Order By: Relevance
“…We attribute the success of ITTREAT to it being a “one‐stop” integrated and non‐judgemental service, which helped mitigate against non‐engagement, corroborated by our qualitative data( 28 ) and a recent systematic review. ( 31 ) The Hepatitis nurse effectively linked all the different components of the service.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We attribute the success of ITTREAT to it being a “one‐stop” integrated and non‐judgemental service, which helped mitigate against non‐engagement, corroborated by our qualitative data( 28 ) and a recent systematic review. ( 31 ) The Hepatitis nurse effectively linked all the different components of the service.…”
Section: Discussionsupporting
confidence: 71%
“…This community model of care was based at a single site in England, the trusting client provider relationship being the key to engagement. ( 28 ) Since this may not be applicable to other geographical sites our study lacks generalisability and external validity to support a national change in service delivery. However, a recent systematic review, involving studies from multiple countries reporting different models of care reported excellent community‐based SVR in PWUDs.…”
Section: Discussionmentioning
confidence: 92%
“…The goal of this qualitative study was to assess the perceptions of PEH, who have been diagnosed with HCV, and treatment providers on the development of culturally sensitive designs to support HCV initiation and completion. Awareness of sociocultural differences is crucial in the design of any successful intervention to achieve HCVsustained virologic response (Phillips et al, 2020). We discovered three major themes which included: Our findings revealed that essentials of successful participant engagement and retention included an appreciation of the support role of the nurse-led CHW as well as the advocacy that they provided.…”
Section: Discussionmentioning
confidence: 89%
“…The aim of our study was to support the evidence that the efficacy of therapy in PWID is high and that the financial resources are invested effectively. Achieving cure of people in the epidemiologically high-risk group, we decrease the risk of disease transmission [ 4 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%